Conversion, Leadership and Identity of the Evangelical Roma in Bulgaria - Slavkova, Magdalena (Roma History and Culture, 2025)
Combining historical and ethnographic approaches in her pioneering study, Magdalena Slavkova offers an insightful contribution to our understanding of Romani evangelicalism. The phenomenon appeared at the beginning of the 20th century in Bulgaria, considerably earlier than many other European countries, with various missionaries working among the Roma, such as Methodists and Baptists among them, as well as later Pentecostals. This book explains the conversion process of men and women from different Romani groups who demonstrate their identity as believers in Jesus Christ and shows how power is transferred from older to younger men and from men to women through mechanisms enabled by evangelism.